PEMANFAATAN FORKLIFT UNTUK KELANCARAN OPERASIONAL DI GUDANG PRODUSEN SUSU KENTAL MANIS - Sulistya Pribadi; Astrin Ayudya; Rini Septiastri Wulandari (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this study is to examine the effect of forklift treatment on the warehouse continuity operation of PT  Frisian Flag Indonesia at Ciracas Plant. The methods of data collection are in the form of field research, library research and data analysis techniques with Likert-scale weighting, simple linear regression analysis, correlation coefficient analysis, determinant coefficient analysis, and hypothesis testing. The conclusion shows that simple linear regression calculation obtained a constant of 17.341 and b regression coefecient was equal to 0.607. Referring to the regression equation, it is seen that every single increase unit of forklift treatment escalation will be followed by an increase in operational activities of 0.607 at the constant 17.341. The result of calculation of correlation coeficient can be assessed that r (correlation) was equal to 0.725. This proved that the increase of forklift treatment had an effect on the opeerational activities since the r values was 0.725. This means there were a positive correlation between forklift maintenance variables and operational activities. The calculated result of coefficient determined in which Kp = r² aqual to 0.725² indicated that the contribution amount of forklift treatment was 52.5% on operational activities, while the remaining 47.5% was the influence of factors outside this research. Hypothesis testing shows taccount  > ttable. That means Ho is rejected and Ha is accepted. Thus, there is a significant positive influence between forklift treatment for warehouse operation.